2022
DOI: 10.1186/s42269-022-00702-6
|View full text |Cite
|
Sign up to set email alerts
|

Oxytetracycline residues in bovine muscles, liver and kidney tissues from selected slaughter facilities in South Western Uganda

Abstract: Background Due to high disease burden and poor animal health services in Uganda, administration of antimicrobials particularly oxytetracycline (OTC) is often done by farm owners and workers without any prescription. This results in misuse of OTC with consequent high chances of antibiotic residues and antimicrobial resistance hence posing public health threat. The degree of public health threat from OTC use is not well established due to limited published data on antibiotic residues and usage in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…18 S imilarly, it was in line with the finding reported from Uganda, which reported that the prevalence of positive samples ranged from 56.88% to 84.52%. 35 Similarly, the finding of the current study was in line with the finding of another study conducted in Iran, which reported 75% of meat samples positive for tetracycline. 36 The findings suggest that oxytetracycline was indiscriminately used in the study areas.…”
Section: Discussionsupporting
confidence: 92%
“…18 S imilarly, it was in line with the finding reported from Uganda, which reported that the prevalence of positive samples ranged from 56.88% to 84.52%. 35 Similarly, the finding of the current study was in line with the finding of another study conducted in Iran, which reported 75% of meat samples positive for tetracycline. 36 The findings suggest that oxytetracycline was indiscriminately used in the study areas.…”
Section: Discussionsupporting
confidence: 92%
“…For example, tetracycline residues have been found at the injection site as many as 35 days after intramuscular administration [ 30 ]. In addition, previous studies have reported that tetracycline residue levels were higher in muscles than in kidneys [ 31 , 32 , 33 , 34 ], regardless of regulations. Future experimental and epidemiologic field studies could generate knowledge on host- and farm-level factors associated with tissue levels of tetracycline residues in food animals in the U.S.…”
Section: Discussionmentioning
confidence: 98%
“…The global population is increasing steadily, and will necessitate a marked increase in food production so as to support the estimated 9.1 billion people expected to exist on planet earth by 2050 [1]. Poultry farming is an agricultural sector which plays, and will continue to contribute a signi cant role in realizing the envisaged food security [2,3]. Chicken (Gallus domesticus L.) is the most domesticated poultry bird in the world, with a global number of 33 billion in 2020 [4].…”
Section: Introductionmentioning
confidence: 99%